Songs for other people's weddings : a novel - Levithan, David; Lekman, Jens; Lekman, Jens (Abrams Press, 2025)
"J is a wedding singer, but it didn't start that way. He wrote a love song for one of his albums that accidentally became an international hit for to-be-wed couples. These days, J talks to couples about all the small, strange things that brought them together-and then he writes and performs an original song at their weddings. But whatever J tries, he can't find the perfect words for his own love with V. Now V is off to New York, helping launch a social media platform that has struck gold. While V's life grows bigger and busier without J in it, he seeks refuge and wisdom in the happy couples he writes for, who all look so unshakably connected. And so, whether through fate or sheer determination, J sets his sights on New York, to see if he can't get V and himself singing in harmony once again. But could it be that the tune of their song changed for good?"--